Removing Discrimination in Public Service: Braille E-Ticket Drug Health Services for People with Visual Disabilities - Fadillah Putra; Rini Puji Lestari (Wacana: Jurnal Sosial dan Humaniora)
Assistive technology in public sector services is an effort to reduce discrimination in public services. Studying bioethics as part of life sciences is important, especially regarding administrative and humanistic bioethics (Becker, 2021). This study aims to analyze the continuity of the BREXIT (Braille E-Ticket Extraordinary Access for Visual Disabilities) innovation in improving the quality of health services for persons with visual disabilities in Malang City, Indonesia. The variables used were the Service Innovation Variable (X) and the Public Service Quality Variable (Y). The data analysis technique used is the Multidimensional Scaling (MDS) method with the software Rapfish (Rapid Appraisal of Fisheries) 3.1 for Windows. The results showed that the BREXIT program succeeded in reducing the perception gap between people with disabilities (visually impaired) compared with non-disabled people, especially in health services at Janti Health Center Malang City, Indonesia.